2019
DOI: 10.4310/jdg/1559786424
|View full text |Cite
|
Sign up to set email alerts
|

Properly immersed surfaces in hyperbolic $3$-manifolds

Abstract: We study complete finite topology immersed surfaces Σ in complete Riemannian 3-manifolds N with sectional curvature K N ≤ −a 2 ≤ 0, such that the absolute mean curvature function of Σ is bounded from above by a and its injectivity radius function is not bounded away from zero on each of its annular end representatives. We prove that such a surface Σ must be proper in N and its total curvature must be equal to 2πχ(Σ). If N is a hyperbolic 3-manifold of finite volume and Σ is a properly immersed surface of finit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…As already observed, a surface Σ appears as a totally umbilic surface with mean curvature H Σ ≥ 1 in a hyperbolic manifold N of finite volume if and only if Σ is a geodesic sphere with H Σ > 1 or it is a flat torus or a flat Klein bottle in a cusp end of N when H Σ = 1. On the other hand, if Σ is a totally umbilic surface with H Σ ∈ [0, 1), which must be proper by item 1, then Corollary 4.7 of [7] implies that the Euler characteristic of Σ is negative, completing the proof of items 2 and 3.…”
Section: Thusmentioning
confidence: 86%
See 2 more Smart Citations
“…As already observed, a surface Σ appears as a totally umbilic surface with mean curvature H Σ ≥ 1 in a hyperbolic manifold N of finite volume if and only if Σ is a geodesic sphere with H Σ > 1 or it is a flat torus or a flat Klein bottle in a cusp end of N when H Σ = 1. On the other hand, if Σ is a totally umbilic surface with H Σ ∈ [0, 1), which must be proper by item 1, then Corollary 4.7 of [7] implies that the Euler characteristic of Σ is negative, completing the proof of items 2 and 3.…”
Section: Thusmentioning
confidence: 86%
“…Suppose that Σ is a totally umbilic surface in a hyperbolic 3-manifold N of finite volume, with finite negative Euler characteristic and H Σ ∈ [0, 1). Then, item 4a follows immediately from [7,Corollary 4.7].…”
Section: Thusmentioning
confidence: 99%
See 1 more Smart Citation
“…Theorem 1.1 contrasts with [6,Proposition 4.8], where it is shown that, for any H ≥ 1 and any noncompact hyperbolic 3-manifold N of finite volume, there exists a complete, properly immersed annulus with constant mean curvature H. Therefore, the hypothesis of embeddedness in Theorem 1.1 is necessary. Moreover, in [1], together with Adams, we proved that for any H ∈ [0, 1) and any surface S of finite negative Euler characteristic, there exists a hyperbolic 3-manifold of finite volume with a proper embedding of S with constant mean curvature H. Furthermore, there are examples of closed surfaces in hyperbolic 3-manifolds of finite volume for any H ≥ 1; namely geodesic spheres and tori and Klein bottles in its cusp ends.…”
mentioning
confidence: 97%
“…We continue the study of properly immersed surfaces of constant mean curvature H in hyperbolic 3-manifolds of finite volume that began with the works of Collin, Hauswirth, Mazet and Rosenberg [2,4] in the minimal case, and was extended to the H ∈ (0, 1) case by the authors [6].…”
mentioning
confidence: 99%